Real-time systems development - Williams, Rob (Elsevier Butterworth-Heinemann, 2006)
Real-time Systems Development is a text for computing students who want to understand more about the development of software for real-time applications, involving concurrent programming, multi-tasking, data i/o and embedded processors.The book has been written to cover single semester final year undergraduate options or MSc modules in the area of real-time systems design and implementation. Assuming a certain level of general systems design and programming experience, this text will extend students knowledge and skills into an area of computing which has increasing relevance in a modern world of telecommunications and ‘intelligent’ equipment using embedded microcontrollers.* Concise treatment delivers material in manageable sections* Includes handy glossary, references and practical exercises based on familiar scenarios* Supporting website contains slides, solutions to problems and software examples